Exploring the nexus of gender and environment in the H2020 PHOENIX project: insights from the design of a gender equality plan - Esteves, Denise; Holz, Sheila; Lopes, Mónica; Sandri, Sinara (Frontiers in Environmental Science, 2024)
Introduction: The H2020-funded PHOENIX project (2022–2025) aims to enhance democratic innovations to implement the European Green Deal (EGD) at local, regional, and national levels, focusing on key policy areas like farm-to-fork, circular economy, energy transition, and healthy soil. Despite the European Green Deal’s ambitious goals for a climate-neutral Europe by 2050, it primarily emphasizes technological solutions and overlooks social vulnerabilities like gender, class, and race. In the light of the European Commission’s efforts to promote gender equality in EU-funded projects through the implementation of Gender Equality Plans (GEPs), the study carried out a comprehensive literature review aimed at gaining insights into the intricate relationship between gender and the environment with a particular focus on the intersection of gender and research and innovation, especially within the context of the European Green Deal. Drawing on their experience as action researchers developing a Gender Equality Plan within the H2020 PHOENIX project, the authors emphasize the importance of gender-sensitive research in environmental projects and underscore the significance of a participatory approach in achieving effective gender change. The lack of reporting on experiences of incorporating a gender perspective has resulted in a significant knowledge gap regarding the various impacts that environmental actions can have on people’s lives, based on their gender. The article endeavours to bridge this gap by achieving two main goals: highlighting the importance of gender-sensitive research in environmental projects and discussing how the gender gap is addressed in the H2020 PHOENIX project through its participatory approach to design the Gender Equality Plan. Methods: This paper reports on the participatory approach adopted within the H2020 PHOENIX project to develop a Gender Equality Plan. This participatory approach draws from literature that underscores the advantages of collaboration in effecting change towards gender equality. This method entailed the active engagement of all project partners during a co-creation session for creating a gender equality plan held during the annual project meeting and has underpinned the comprehensive PHOENIX gender mainstreaming framework. Findings and discussion: The results of the co-creation session for creating a Gender Equality Plan provided a robust foundation for the comprehensive approach to mainstreaming gender within the PHOENIX project that could guide the project towards a more gender-sensitive research. This analytical and planning phase, despite being an early stage, became the cornerstone of the gender equality plan and also defined the specific steps and actions needed to address the gender topic effectively within the consortium. This process led to the identification of strategic goals and actions aligned with specific goals of the project and intertwined with the challenges of the Democratic Innovations’ capacity of developing their full transformative potential when dealing with environmental topics. The strategic goals were then transformed by the PHOENIX partners into levels of observation and specific actions to be adopted within the consortium.